Pelaksanaan Pemenuhan Hak Atas Aksesibilitas Pendidikan Tinggi Bagi Penyandang Disabilitas Di Yogyakarta - Eko Riyadi (Jurnal Hukum IUS QUIA IUSTUM, 2021)
There are two backgrounds to this research, namely the mandate of the Convention on the Rights of Persons with Disabilities and Law Number 8 of 2016 to provide inclusive education for persons with disabilities, and conditions of higher education services and facilities that are not yet suitable for access for persons with disabilities. This research was conducted to answer two questions, first, how is the portrait of the fulfillment of the right to education for persons with disabilities in tertiary institutions in Yogyakarta? Second, how is the analysis of human rights law on the practice of fulfilling the right to education for persons with disabilities at universities in Yogyakarta? The answer to this question is done by conducting empirical research. This study concludes that the accessibility of high education for persons with disabilities is still very low. Educational services and infrastructure still prevent persons with disabilities from gaining access to higher education. This also shows that higher education has not been able to fulfill the right to education for persons with disabilities. In the future, it is time for higher education providers to prepare aspects of services and infrastructure that are accessible for persons with disabilities.-